VD_FINDINFO Jug / 2025 / 3 vom 4. Februar 2025 - VD Tribunal cantonal (2025)
CLAH 80, ENLÈVEMENT D'ENFANTASPECTS CIVILS, FRANCE, ADMISSION DE LA DEMANDE | 13 al. 1 let. a CLaH 80, 13 al. 1 let. b CLaH 80, 3 al. 1 CLaH 80